Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1123/ijsnem.2018-0377
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Plasmacytoid Dendritic Cell-Stimulative Lactic Acid Bacteria, Lactococcus lactis Strain Plasma, on Exercise-Induced Fatigue and Recovery via Immunomodulatory Action

Abstract: The unique lactic acid bacteria, Lactococcus lactis strain plasma (LC-Plasma), stimulates plasmacytoid dendritic cells, which play an important role in viral infection. The authors previously reported that LC-Plasma reduced the number of days athletes experienced cold-like symptoms and fatigue feelings after high-intensity exercise training; however, the mechanism was unclear. In this study, the authors investigated the effect of LC-Plasma on recovery from physical damage after single exercise on a treadmill i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
0
9
0
1
Order By: Relevance
“…paracasei 8700:2 in healthy individuals reduced the risk of acquiring common cold infections and pharyngeal symptoms (Berggren et al 2011). A study conducted by Kokubo et al (2019) showed Lactococcus lactis LC plasma affects plasmacytoid dendritic cell activation. This attenuates muscle degenerative genes and the concentration of fatigue-controlled cytokine transforming β-growth factor.…”
Section: Probiotics and Control Of Viral Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…paracasei 8700:2 in healthy individuals reduced the risk of acquiring common cold infections and pharyngeal symptoms (Berggren et al 2011). A study conducted by Kokubo et al (2019) showed Lactococcus lactis LC plasma affects plasmacytoid dendritic cell activation. This attenuates muscle degenerative genes and the concentration of fatigue-controlled cytokine transforming β-growth factor.…”
Section: Probiotics and Control Of Viral Infectionsmentioning
confidence: 99%
“…Lb. rhamnosus M21 upon treatment for pneumonia in mice showed increased levels of interferon-γ and interleukin-2, which are representative cytokines of type I helper T cells (Song et al 2016) Lactobacillus plantarum Gastroenteritis coronavirus (TGEV) Diminishes granulocyte, reduces virus recovery Yang et al 2017 Lactococcus lactis JCM 5805 RTI, common infectious disease Activates plasmacytoid dendrtitic cell Kokubo et al 2019 Lactobacillus plantarum CRL1506 Gastroenteritis coronavirus (TGEV) Diminish inflammatory-mediated tissue damage Yang et al 2017 Bacillus subtilis OKB105 Gastroenteritis coronavirus (TGEV) Inhibits viral adherence by competitive inhibition Wang et al 2017 ( Table 1). Application of probiotics has demonstrated clinical potential in animal experiments.…”
Section: Probiotics and Control Of Viral Infectionsmentioning
confidence: 99%
“…Furthermore, the bacterial strain decreased fatigue accumulation during consecutive high intensity exercise. A later study in mice showed that LC-Plasma-activation of pDC in turn attenuates the concentration of fatigue controlled cytokine TGF-β and muscle degenerative genes [154]. Consumption of a probiotic powder containing L. rhamnosus GG and Bif.…”
Section: Impact Of Environment and Life Stage On Gut Microbiota Anmentioning
confidence: 99%
“…Это указывает на то, что противовирусный механизм действия пробиотиков может быть независимым от TLR [68]. Исследование, проведенное T. Kokubo et al, показало, что Lactococcus lactis LC влияют на активацию плазмоцитоидных дендритных клеток [78]. Это ослабляет гены дегенерации и концентрацию контролируемого цитокина, трансформирующего β-фактор роста.…”
Section: пробиотики обладают противовирусной активностьюunclassified